EVALUASI NILAI EMP MKJI 1997 MENGGUNAKAN METODE TIME HEADWAY PADA SIMPANG EMPAT BERSINYAL KOTA MATARAM (STUDI KASUS DI SIMPANG JL. PANCA USAHA – JL. BUNG HATTA DAN SIMPANG DI JL. DR. SUJONO – JL. TGH LOPAN KOTA MATARAM) - HASYIM HASYIM; ROHANI ROHANI; MAYA NURFADILLAH (Universitas Mahasaraswati K. Mataram, 2024)
Traffic flow consists from various types of vehicles, and it requires a conversion value to represent the traffic flow more accurately in terms of the standard vehicle type, namely passenger cars, commonly referred to as Passenger Car Units (PCU). The conversion factor from different types of vehicles to passenger cars is called Passenger Car Equivalence (PCE). In calculating road capacity in Indonesia, the PCE value used refers to Manual Kapasitas Jalan Indonesia (MKJI) 1997.In this study, a method called the time headway method is used to determine the Passenger Car Equivalence (PCE) value. This method involves recording the convoy of vehicle pairs per green time. The time headway value is obtained from the time difference between two vehicles passing a reference line, which is the stop line, calculated from the front bumper of the preceding vehicle to the front bumper of the following vehicle.Based on the research results, the PCE value using the Time Headway method for motorcycles (MC) at a three-phase intersection located at the signalized intersection of Panca Usaha Street - Bung Hatta Street is 0.57. Meanwhile, at a four-phase intersection located at the signalized intersection of Dr. Sujono Street - TGH Lopan Street, the PCE values for motorcycles (MC) and heavy vehicles (HV) are 0.34 and 2.23, respectively. There are differences in PCE values between MKJI 1997 and the results of the Time Headway method calculation for protected-type signalized intersections, which are 0.2 for motorcycles (MC) and 1.3 for heavy vehicles (HV). These differences occur due to changes in field conditions, such as an increase in the number of vehicles in the intersection arms and changes in green time at intersections